Legal Review and Democratic Challenges of Community Organizations in Indonesia - Waluyo Slamet Pradoto; Santoso Budi Nursal Umar (Lembaga Pengembangan Kinerja Dosen, 2025)
This research discusses the phenomenon of social organizations (ormas) in Indonesia from a legal perspective and the challenges of democracy. The freedom of association guarantyd by Article 28E paragraph (3) of the 1945 Constitution serves as the legal basis for the existence of social organizations, which are further regulated by Law Number 17 of 2013 and Law Number 16 of 2017. Regulatory changes, particularly the government's authority to dissolve mass organizations without judicial process, have sparked a debate between the need to maintain public order and the guaranty of the principle of due process of law. The research method used is normative juridical with a legislative and conceptual approach, supported by a literature study from primary and secondary legal materials. The study results show that although mass organizations have great potential in strengthening democracy, challenges such as identity politics, radicalism, lack of funding transparency, and state power abuse against mass organizations still pose major obstacles. Therefore, balanced legal regulations, transparent oversight, and enhanced democratic literacy are needed to ensure that the role of social organizations remains in line with the principles of the rule of law and Pancasila democracy.